2006
DOI: 10.1016/s0022-5347(05)00170-9
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Reperfusion Injury in Cadaveric Nonheart Beating, Cadaveric Heart Beating and Live Donor Renal Transplants

Abstract: NHBD renal transplants were accompanied by a greater release of free radicals at reperfusion (NHBD > HBD > LD), which was associated with an increase in tissue injury markers at reperfusion. This was reflected in a slower return to stable renal function in NHBD compared to HBD and LD renal transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The current results suggest that severe ischemic damage may limit the regeneration process and result in a decreased proliferation of renal cells, which could be associated with persistent abnormalities in perfusion. These data are consistent with a recent study which showed that recovery was slower in NHBD transplants than in live donor transplants (7).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current results suggest that severe ischemic damage may limit the regeneration process and result in a decreased proliferation of renal cells, which could be associated with persistent abnormalities in perfusion. These data are consistent with a recent study which showed that recovery was slower in NHBD transplants than in live donor transplants (7).…”
Section: Discussionsupporting
confidence: 93%
“…These changes were associated with improved kidney function, reduced DGF, and a lower rate of PNF. Recent studies showed that renal recovery from NHBD transplants continues for 3 mo after hospital discharge (7). In the pig model, renal recovery was delayed and was associated with increased protein excretion in the urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischaemia-reperfusion injury consist of 2 injury mechanisms namely ischemia characterized as oncotic necrosis and reperfusion injury. In the clinical setting this damage may delay the recovery of renal function prolong or complicate postoperative recovery or precipitate immunological reactions involved in the subsequent rejection reaction42.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia time is one of the important factors impacting transplantation results [14,15]. Ischemia itself can cause severe damage because of the potential for a build-up of metabolic wastes.…”
Section: Discussionmentioning
confidence: 99%